DEFINITION OF PSYCHOLOGICAL FEATURES PERSONAL AND PROFESSIONAL FORMATION FUTURE FOREIGN LANGUAGE TEACHER - D.Ye. Barasheva (Academy of Cognitive and Natural Sciences, 2008)
The article is devoted to the study of psychological peculiarities of a future foreign language teacher personal and professional development. Selfidentification is stipulated in this work as the criteria of personal and professional peculiarities of the development of a future foreign language teacher. Personal and professional peculiarities of a future foreign language teacher's development are differentiated. The former include tendencies for identification personal: a) self-existence; b) self reflection in interpersonal communication; c) role in social life and activity. The latter refer to the following peculiarities: a) personality faces a necessity of appropriating the image of a creative reorganizing profession (which is pedagogue); b) language teacher's professional image implies development of a subject's activity in the sphere of inter-subjects' communication; c) the specialty of foreign language teachers demands the identification of the future foreign language teachers in the culture of a foreign language they teach. The data of theoretical and empirical research demonstrate a certain misbalance in integration of personal and professional emotive-cognitive constructs, which motivates further search of psychological ways for making the process harmonically balanced.